Correction: Rational design of functionalized polyacrylate-based high internal phase emulsion materials for analytical and biomedical uses. Issue 48 (28th November 2016) - Brusotti, Gloria; Calleri, Enrica; Milanese, Chiara; Catenacci, Laura; Marrubini, Giorgio; Sorrenti, Milena; Girella, Alessandro; Massolini, Gabriella; Tripodo, Giuseppe
Abstract : Correction for 'Rational design of functionalized polyacrylate-based high internal phase emulsion materials for analytical and biomedical uses' by Gloria Brusotti et al., Polym. Chem., 2016, DOI: 10.1039/c6py01992g.